Pengaruh Penyuluhan Anatomi Fisiologi Reproduksi Wanita Dalam Meningkatkan Pengetahuan Remaja - Sartika, Yuli; Husuni, Wa Ode Sitti Fidia (Madu : Jurnal Kesehatan, 2023)
Teenagers are an age that is vulnerable to experiencing social upheaval because their emotional development is not yet stable and the increasing popularity of various kinds of spectacles obtained via the internet and social media, makes teenagers imitate doing negative things. Adolescents really need basic knowledge regarding the anatomy and physiology of the reproductive organs, which is of course closely related to fertility and sexuality issues, especially the morphology and function of the reproductive organs. The aim of this research is to determine the effect of counseling on the anatomy and physiology of female reproduction in increasing the knowledge of young women in Kontunaga. The research method uses the Pre-Experiment Design method with One Group Pretest-Posttest Design. The analysis technique uses the Wilcoxon Matched Pairs Test, the sampling technique uses Total Sampling, namely 29 young women. The research results showed that the calculated Z value was -3.260 and the significance value was 0.001 (p<0.05), so Ha was accepted, meaning that there was a significant influence between before and after the counseling was given.